ANALISIS MODUS NORMAL DAN KEKUATAN STRUKTUR SIRIP ROKET-168 DARI BAHAN AL-PLATE - Sugiarmadji HPS; Setiadi (Indonesian Journal of Aerospace, 2004)
Structural strength analysis on Motor Rocket-168 fins was carried out to determine static stresses due to aerodynamic loadings. Here, 90 mm of the root chord area from leading edge was unclamp (free). The analysis results showed the maximum value of von Mises stress is Q von mises = 42.40 MPa. For 90 mm condition un clamp (free) we obtained the safety factor of the material for fins structures made of Al-Plate is SF=3.39. For 67.5 mm of 90 mm root chord area constrainted at 12456 directions, it was found Qvm equal 11,26 MPa and has higher safety factor. Eigenvalues and eigenvectors of the fins structures. The results showed that the eigenvalues of the fin structures are Q1 equal 198,47 Hz, Q2 equal 616,34 Hz, Q3 equal 1080,97 Hz, Q4 equal 1704,33 Hz, Q5 equal 2386,82 Hz, dan Q6 equal 2770,94 Hz.